Strategi Pengembangan Pariwisata Ramah Muslim Berbasis Ekonomi Hijau dengan Pendekatan SWOT dan AHP di SPTN Wilayah II Pulang Pisau - Suherman; Bhayu Rhama; Nurlia Eka Damayanti; Wiwin Zakiah; Winner Petra Telaumbanua; Ulan; Dede Ardiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study aims to analyze the development of Muslim-friendly tourism based on a green economy framework in SPTN Region II Pulang Pisau, Sebangau National Park. A mixed methods approach with a sequential explanatory design was employed, utilizing observations, in-depth interviews, Focus Group Discussions (FGD), and strategic analysis using SWOT (IFAS–EFAS) and the Analytical Hierarchy Process (AHP). Informants were selected through purposive sampling based on expert judgment, involving seven key participants. The results indicate that the area is positioned in the hold and maintain quadrant (IFAS 2.51; EFAS 2.65), suggesting that development efforts should focus on strengthening fundamental aspects. Key potentials include the high biodiversity of the peatland ecosystem, strong support from conservation partners, and active community participation. However, major constraints include limited infrastructure, suboptimal halal facilities, and the high risk of forest and peatland fires. The AHP results identify priority strategies, including strengthening partnerships for fire mitigation (0.403), improving halal tourism facilities (0.321), and enhancing conservation-based branding (0.276). Therefore, development should be implemented in a gradual, collaborative, and adaptive manner to maintain a balance between ecological sustainability, spiritual needs, and economic development.